Wound burden: A point prevalence study at an academic hospital in Western Kenya - Julie Zuniga; Margaret Mungai; Moureen Adhiambo; Mary Kwambai; Lorna Obanda; Hellen Jemeli; Bernedicta Chepkorir; O’Brien Kyololo; Mary Kay Foster; Beth Altenburger; Dinah Chelagat; Rodica Muraru; et al. (International Journal of Africa Nursing Sciences)
Background: Low- and middle-income countries carry a high burden of wounds. In such countries, the prevalence and extent of wound burden are hard to quantify because of systemic barriers associated with limited resources. In this study, we report the prevalence of patients presenting with wounds at a regional hospital in Kenya and describe these patients’ characteristics. Methods: A descriptive study of inpatients and outpatients presenting wounds was conducted in Kenya’s teaching and referral hospital. Data on patient characteristics, wound and wound care characteristics, and social determinants of health were collected. Findings: The data comprise point-in-time information for wound prevalence and wound types. Participants (N = 122) were primarily inpatients (68.9 %); 55 % were male. Traumatic chronic wounds were the most prevalent (35.2 %), followed by burn injuries (18.8 %), diabetic foot ulcers (12.3 %), and pressure injuries (9.8 %). Many of the patients (77.9 %) worried at some point that food for their family would run out before they could obtain enough money to buy more, and 75 % reduced their meal portions because they lacked funds to buy sufficient food; almost half (44.1 %) had felt hungry but did not eat due to lack of money to purchase sufficient food for their families. Conclusion: Patients had extensive and multiple wounds, with a history of wounds that were slow-healing, and a large majority suffered from food insecurity. Without addressing social determinants of health, the burden of wound care will remain high in this region.